FRI0168 Comprehensive Analysis of the Oral Microbiome in Axial Spondyloarthritis Reveals Associations with Disease Activity and Periodontitis. (10th June 2014) - Bisanz, J.E.; Suppiah, P.; Thomson, M.; Milne, T.; Yeoh, N.; Nolan, A.; Ettinger, G.; Reid, G.; Gloor, G.B.; Burton, J.; Cullinan, M.; Stebbings, S.
Abstract : Background: A wealth of data supports a role for the microbiome in the pathogenesis of spondyloarthtritis (SpA). To date, studies have concentrated on the intestinal tract, which harbours the largest and most diverse microbiota. However, the oral microbiota is also notable in its diversity and has recently been the focus of interest as a potential factor in the pathogenesis of rheumatoid arthritis. Recent studies have demonstrated a higher prevalence of periodontitis in patients with ankylosing spondylitis, raising the possibility that exposure to the oral microbiome through a compromised mucosal barrier may be a factor in the pathogenesis of SpA. Objectives: To investigate the oral cavity as a site of chronic inflammation in axial spondyloarthritis (AxSpA) and to compare profiles of microbial communities which colonise the oral cavity in health and AxSpA. Methods: Thirty nine participants, 17 with AxSpA and 22 age and gender matched, disease free controls, were recruited. Disease activity in patients with AxSpA was assessed using the Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) and CRP. All participants underwent a detailed dental examination including assessment of probing pocket depth (PPD), clinical attachment loss (CAL), bleeding on probing (BOP), plaque index, oral mucosal conditions, and caries status. Plaque samples were obtained and their bacterial populations were profiled using Ion Torrent sequencing of the V6 region of the 16S rRNA gene. Results: Patients with AxSpA had active disease (BASDAI Mean ± SD 4.1±2.1) and had significantly greater prevalence of both periodontitis (PPD≥4mm at ≥4 sites) and a higher plaque index than controls (P=0.008 and P=0.006 respectively). Analysis of bacterial communities showed no difference between AxSpA patients and healthy controls, either in their overall within sample organism diversity or in community structure between groups. However, analysis at the level of operational taxonomic units (OTU) demonstrated a significant association between AxSpA and several bacteria including Campylobacter spp. and Actinomycetes spp . Additionally, certain OTUs were present in higher relative abundances in patients with active AxSpA (see Table). Conclusions: Patients with AxSpA have a higher prevalence of periodontitis. Analysis of plaque communities suggests that certain bacteria are more prevalent in the periodontal tissues of patients with AxSpA and associates with active disease. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3406